Business Planning : Pro Evolution Sport (PES) Sdn. Bhd. / Mohd Zulhairi Yusoff ...[et al.] - Yusoff, Mohd Zulhairi; Ismail @ Adnan, Zarul Iqbar; Ishak, Amyrol; Jasman, Muhd Aqis Hakim (2010)
Our company is developing in January 2010. Its located at Bandar Baru Pasir Pekan, Kota Bharu. Our company’s location is opposite of the Maybank building which are easily found. Our company supply and provide the variety brand of sportswear and equipment such as ADIDAS, NIKE, JOMA, KAPPA, UMBRO, LOTTO, DIADORA, PUMA, KRONOS, FILA, ASCICS, FIGOS, EVERLAST, YONEX and many more types of brands. We were registered as a partnership business represented by four members. Our shop location was located in town centre. We choose this location because we can see the potential that can give us advantages and profited. The potential we can see is that the location is strategic because of we are surrounded with huge community which are mostly interested in sport like football, futsal, basketball and many more. Pro Evolution Sport (PES) was startup the trading business which buys the product with the production company in a large of scale and sells that product. We choose original and high quality product to satisfy the sport lifestyle.